Effect of He-irradiation fluence on the size-dependent hardening and deformation of nanostructured Mo/Zr multilayers. (December 2018) - Wu, S.H.; Cheng, P.M.; Wu, K.; Hou, Z.Q.; Wang, Y.Q.; Liang, X.Q.; Li, J.; Kuang, J.; Zhang, J.Y.; Liu, G.; Sun, J.
Abstract: Previous studies demonstrated that the He ion irradiation damage tolerance of nanostructured metallic multilayers (NMMs) was closely dependent on the layer thickness ( h ): smaller h led to lower irradiation hardening. Here in Mo/Zr NMMs, we uncovered that the h -dependent irradiation hardening and corresponding plastic deformation characteristics are also sensitive to the He + irradiation fluences. At a low irradiation fluence of 1.0 × 10 16 He + ·cm −2, the irradiation hardening decreased monotonically with reducing h . While at a high irradiation fluence of 1.0 × 10 17 He + ·cm −2, a non-monotonic h -dependence was unexpectedly displayed with the minimum irradiation hardening at h of ∼25 nm. The irradiation fluence also affects the strain rate sensitivity ( m ) remarkably. Irradiation of 1.0 × 10 16 He + ·cm −2 induced a transition in SRS m from positive in the as-deposited Mo/Zr NMMs to negative SRS in their irradiated counterparts. This transition was rationalized in terms of dynamic strain aging that considered dislocation-bubble interactions. Irradiation of 1.0 × 10 17 He + ·cm −2, however, resulted in a non-monotonic h -dependence of m, with the bottom located at a turning point of h ∼50 nm. Coupling effect of the layer thickness and the applied fluence on irradiation hardening and plastic deformation characteristics was quantitatively elucidated by employing a strengthening model and a thermally activated model, respectively, where parameters of the characteristic microstructural features, i.e ., the layer thickness and irradiation (He) defects, were both included. Graphical abstract: Highlights: The Mo/Zr NMMs with smaller h display the greater radiation resistance with a lower bubble density. Under the high-fluence irradiation, a critical thickness h (∼15 nm) exists below which the irradiation hardening becomes more significant. The low-fluence irradiated Mo/Zr NMMs present the negative SRS m, while the high-fluence irradiated Mo/Zr NMMs present the non-monotonic size-dependent positive SRS m.